Cash Settled Commodity Option Contracts as an Alternative to Minimum Support Price: A Mechanism to Alleviate Farmer Distress - Rama Murthy Y, Sree (Information Management and Business Review, 2020)
Cash settled commodity options is a possible alternative to create a mechanism so that minimum support prices work in reality and do not remain a paper exercise. This paper argues that the government should create a commodity options market for all minimum support price (MSP) commodities. Further option contracts should be cash settled. The government should participate by selling put options at or above the minimum support price, so that farmers can exercise the option if they find that market prices are below the minimum support price.